The Impact of China’s Foreign Direct Investment on Economic Growth of Lao PDR - XAYSOMBATH, Sompatthana; Yuan Fei, Xiao (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
For the researcher on the impact of Chinese foreign direct investment (FDI) on economic growth of Lao PDR in this paper, researcher used time series data from 2000 to 2019 and implied it with the Ordinary Least Squares (OLS) and Ordinary Least Squares Robust (OLS robust). The results indicated that Chinese FDI has positive significant effect on real GDP growth of Laos but it has lower impact than population growth rate. Which 1% of increasing in the population growth rate will affect the real GDP growth of Laos decrease by .55% because most of Lao labor force are low skills and could not participate in economic development as much as possible and 1% increasing of Chinese FDI inflows to Laos will generate the real GDP growth increase by .19% respectively. In addition, the constant has more effect than FDI and population growth, meaning that although there is no inflow of Chinese FDI and population growth but the economic growth of Laos remain growth an average of 4.89% per year. As the outcome of analysis, it is a basic important information for relative partners to find the ways to attract more FDI and try to improve labor skills because an increase in the skilled population will have a positive effect on economic growth (Kremer, M. 1990) and another macroeconomic factor excluded in this model should be taken into the decision. In the paper, the observations are small therefore further researchers should be considering penal data and other macroeconomic factors should be taken into the model because it will give more effective results.